2022
DOI: 10.17221/1/2022-cjgpb
|View full text |Cite
|
Sign up to set email alerts
|

Advances in wheat breeding for resistance to Fusarium head blight

Abstract: Fusarium head blight (FHB), mainly caused by Fusarium graminearum, is one of the most devastating diseases of wheat globally. FHB causes an extensive reduction in yield and reduces the grain quality through its contamination with Fusarium toxins such as deoxynivalenol (DON), T2 toxin, HT-2 toxin, nivalenol, and zearalenone. This review provides an overview of updated progress of genetic studies on the resistance to FHB, with an emphasis on the sources of resistance to FHB, resistance gene/quantitative trait lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 151 publications
0
2
0
Order By: Relevance
“…Fusarium head blight (FHB) incited by Fusarium graminearum (FG) fungus is ranked as the one of the prime annihilating fungal diseases of wheat ( Triticum aestivum L.) globally [ 1 ]. The published literature indicated that this disease drastically reduces the crop yield, leading to huge economic losses [ 2 , 3 , 4 ]. It has been noticed that yield losses are primarily linked with poor quality seed production.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fusarium head blight (FHB) incited by Fusarium graminearum (FG) fungus is ranked as the one of the prime annihilating fungal diseases of wheat ( Triticum aestivum L.) globally [ 1 ]. The published literature indicated that this disease drastically reduces the crop yield, leading to huge economic losses [ 2 , 3 , 4 ]. It has been noticed that yield losses are primarily linked with poor quality seed production.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, fungicide (e.g., Tebuconazole, Triazoles, Prochloraz, etc.) sprays are important methods to preclude and conquer FHB disease in a short time and lessen Fusarium toxins production, despite agro-ecological and resistance development problems [ 2 , 18 , 19 , 20 ]. Hence, the deployment of FHB-resistant varieties is a sustainable, cost-effective, and environmentally friendly approach to FHB management.…”
Section: Introductionmentioning
confidence: 99%